2019
DOI: 10.7554/elife.43627
|View full text |Cite
|
Sign up to set email alerts
|

Flura-seq identifies organ-specific metabolic adaptations during early metastatic colonization

Abstract: Metastasis-initiating cells dynamically adapt to the distinct microenvironments of different organs, but these early adaptations are poorly understood due to the limited sensitivity of in situ transcriptomics. We developed fluorouracil-labeled RNA sequencing (Flura-seq) for in situ analysis with high sensitivity. Flura-seq utilizes cytosine deaminase (CD) to convert fluorocytosine to fluorouracil, metabolically labeling nascent RNA in rare cell populations in situ for purification and sequencing. Flura-seq rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 81 publications
2
41
0
1
Order By: Relevance
“…These data are consistent with recent evidence suggesting that cancer cells from disparate origins may converge to adopt similar metabolic phenotypes in a given organ. [54][55][56] In support of this hypothesis, we demonstrated that expression of catalytically active PHGDH in a non-brain trophic tumor cell line enables brain metastasis, while catalytically inactive PHGDH is far less efficient at promoting brain metastasis. Suppression of PHGDH decreases brain metastatic burden and improves the survival of mice with brain metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…These data are consistent with recent evidence suggesting that cancer cells from disparate origins may converge to adopt similar metabolic phenotypes in a given organ. [54][55][56] In support of this hypothesis, we demonstrated that expression of catalytically active PHGDH in a non-brain trophic tumor cell line enables brain metastasis, while catalytically inactive PHGDH is far less efficient at promoting brain metastasis. Suppression of PHGDH decreases brain metastatic burden and improves the survival of mice with brain metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…Thiol (SH)-linked alkylation of the metabolic labeling of RNA in tissue (SLAM-ITseq) eliminates the noise associated with the purification of RNAs that are not thiol tagged in TU-tagging method (Matsushima et al, 2018), but undesired TU tagging through endogenous enzymes in cells lacking UPRT expression remains a limitation. We described the development of Flura-seq, a cytosine deaminase (CD)-based method for in situ transcriptomic profiling of rare cell populations that represent as little as 0.003% of an organ (Basnet et al, 2019). Flura-seq requires exogenous expression of CD, a key enzyme of the pyrimidine salvage pathway in fungi and prokaryotes (Mullen et al, 1992) and UPRT from T. gondii.…”
mentioning
confidence: 99%
“…5-FU is endogenously converted to fluorouridine triphosphate (F-UTP), which is then incorporated into RNA. The co-expression of UPRT limits the labeling of RNA in the cells expressing CD(Basnet et al, 2019). Flura-seq is applicable to in vitro co-culture experiments as well as in vivo experiments where cells of interest, expressing CD-UPRT, are present in the intact tissue.…”
mentioning
confidence: 99%
“…Exploiting additional hits scoring ex vivo but not in vitro are of particular interest since their targets (MEK1/2, CDKs, RAF1, BRAF, VEGFR2, TOP-1, DNA-PK, PI3K, ATR) might be key during organ colonization. Adaptation of cancer cells to a new organ involves molecular changes at various levels including the transcriptome, metabolome or proteome of cancer cells (Basnet et al, 2019;Park et al, 2011;Sevenich et al, 2014). These changes that are only detected in situ (i.e.…”
Section: Discussionmentioning
confidence: 99%